Plasmid-mediated quinolone resistance determinant qnrB19 in non-typhoidal Salmonella enterica strains isolated in Venezuela - Fanny González; Lucia Pallecchi; Gian María Rossolini; María Araque (Journal of Infection in Developing Countries)
This item has no abstract. Follow the links below to access the full text.